Employment of ethnography research to ensure effective delivery of medical education and clinical training - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2021)
Ethnography is one of the qualitative approaches, wherein the researcher gets submerged into the study setting that has to be explored. An extensive search of all materials related to the topic was carried out in PubMed and a total of five articles were selected based upon the suitability with the current review objectives. The ethnography approach gives a sense of freedom to the researchers to understand in depth the multiple variables in clinical settings or in the delivery of medical education, as the approach remains open ended. In fact, the generated evidence helps the administrators or teachers to understand the dynamics and the root cause of the problem, which then can be effectively sorted out. In conclusion, the application of ethnography empowers the administrators to get a better understanding of the issues in the delivery of medical education and health care. The need of the hour is to encourage training of faculty members in qualitative research, as a trained ethnographer can utilize their skills for the better understanding and effective resolution of the issues impacting effective curriculum delivery.